Analysis of the incidence of changes in the cytopathological examinations of the cervix in the UBS Palmeiras in the city of Cascavel-PR in the period from 2019 to 2020 (Research, Society and Development, 2023)
Cytopathological examination of the cervix is ​​performed in women to detect cellular alterations in the cervix, which may indicate precursor lesions of cervical cancer and even the cancer itself. The main causative agent of cervical cancer (CCV) is the high-risk human papillomavirus (HPV). CCV is the second most common in women worldwide, being more prevalent in developing countries. The objective of this work is to carry out a quantitative survey through the analysis of the record of alterations found in the female population residing in the Alto Alegre neighborhood that attends the Basic Health Unit of Palmeiras. Materials and methods: the book of records of the Basic Health Unit Palmeiras in the city of Cascavel/PR was analyzed, in which the results of cytopathological tests are noted. Results: In 2019, 6.49% of the samples obtained showed important changes. In 2020, 2.35% of the exams collected showed significant changes. The injury that appeared the most in both years was the low-grade injury. Conclusion: With this work, it is expected that the results obtained will serve as a warning for health professionals so that they can guide the referred population about the importance of carrying out the cytopathological examination, the damage that the disease can cause and the forms of prevention.